SIMULATIONS OF IMPROVED BLIND ELECTRONIC DIGITAL SIGNATURES 2D TYPE FOR INFORMATION PROTECTION SYSTEMS - KRASILENKO, VLADIMIR; NIKITOVICH, DIANA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article considers aspects of application of matrix modifications of RSA cryptosystem for creation on the basis of matrix models and algorithms of cryptoconversions of images of blind electronic digital signatures (BEDS). The advantage of the proposed matrix models of RSA is to take into account the specifics of images and ease of adaptation to different types and formats of images. Formulas and algorithmic steps of BEDS creation procedures and intermediate steps of closing, encrypting and decrypting images are given. Model experiments in the Mathcad Professional software environment, screens from the created software modules demonstrate the functionality and advantages of procedures and algorithms for creating improved blind EDS of matrix type for textual documents (TGD) of a confidential nature. The results of modeling the processes of creating such signatures for large-format documents in the Mathcad software environment confirmed the adequacy of the proposed transformation models and the correct operation and verification of BEDS and allowed to determine the processing time and limitations of relevant cryptographic transformations. Improved BEDS take into account the specifics of TGD, adapt to different formats, have better temporal, histogram-entropy characteristics (shown an increase in the entropy of BEDS to 7.98 bits/el.).
Keywords: cryptography; matrix models; blind electronic digital signatures; Mathcad Professional; modeling; text document; encryption-decryption of images; cryptographic transformations of image intensity; nonlinear processing